JURIDICAL IMPLICATIONS OF SPIN OFF AT PT PLN (PERSERO) REVIEWED FROM THE PERSPECTIVE OF LEGAL PROTECTION FOR WORKERS - Ferdiyan Ganesha; Thamrin S; Abdul Thalib (International Conference On Law And Social Sciences, 2024)
One of the corporate actions carried out by companies in the form of limited liability companies is restructuring to achieve competitiveness and competition to meet market demands and maintain their existence. One of the restructurizing carried out is through impure separation (spin off) towards one of the business units which has an impact on the organizational structure and changes in the status of workers in the limited liability company. The separation mechanism is impure (spin off) This group company in a State-Owned Enterprise (BUMN) has not been specifically regulated in a regulation, giving rise to multiple interpretations and different interpretations in practice. Therefore, this topic is important to be researched in this article. This research method uses normative research based on secondary data. The results of the research can be concluded that the workers' working relationship with the parent company has been broken since they were transferred to a subsidiary company and the transfer of workers to another company without a transfer agreement does not provide legal protection for workers' normative rights. So that the government makes implementing regulations for the Employment Law that regulates technically group companies and mechanisms for transferring workers from parent companies to subsidiary companies.